PENGARUH MOTIVASI DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI - Agus Budi Purwanto (BBM (Buletin Bisnis & Manajemen), 2015)
This study aims to determine the effect of motivation and emotional intelligence to employee performance. The research sample was determined by proportional random sampling method. Research data collection techniques by spreading questionnaires to employees of villages in the city of Semarang systematically arranged with multiple choice answers are easy to understand. The research sample is determined by slovin numbered 90 people. Previously conducted research with the instrument test validity and reliability. This study uses multiple linear regression model. The research proves that there is a positive and significant impact either partially or simultaneously motivation and emotional intelligence to employee performance.Keyword : motivation, emotional intelligence, employee performance